#TITLE_ALTERNATIVE# - MANGESTHY HATI MARIA (12810016); Pembimbing : Dr. Nurjanna Joko Trilaksono, PRIMA
This study investigates about the comparison between reanalysis data to compare their skill in the research of Borneo Vortex and cold surge phenomena and to choose which data is the best one. This study use three different reanalysis data, those are NCEP-NCAR, ECMWF ERA-Interim, and JRA-55. The study period is 21 years, starts from December 1991 until February 2012. Only the data at Northern Hemisphere winter monsoon period (December-January-February) is used. The data at cycle 00 UTC and cycle 12 UTC is used. This study examines the reanalysis data comparison of identified Borneo Vortex and cold surge frequency, wind parameter, moisture transport parameter, and interaction between the phenomenon timing.The comparison result of event frequency, frequency match event between data reanalysis, frequency trend, distribution of vortex center, the vortex center position trend, cold surge wind speed (both of histograms and probability density function), the parameters of moisture transport, as well as the interaction time between the occurrence Borneo Vortex and cold surge shows the correlation range inter-reanalysis data is 0.6-0.9 and shows an increasing trend for Borneo Vortex and cold surge frequency within 21 years. The reanalysis data shows no significant difference and any data can still be used and chosen for next Borneo Vortex and cold surge study in the future.